2022
DOI: 10.3390/plants11192601
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Anatomic Characteristics of Stems in Two Alfalfa Genotypes

Abstract: Stems are more important to forage quality than leaves in alfalfa. To understand lignin formation at different stages in alfalfa, lignin distribution, anatomical characteristics and transcriptome profile were employed using two alfalfa cultivars. The results showed that the in vitro true digestibility (IVTD) of stems in WL168 was significantly higher than that of Zhungeer, along with the significantly lower neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin contents. In addition, Zhungeer exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 60 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…Moreover, several reports showed that forage growth is accompanied by increased lignin content with secondary cell wall thickening, which limits forage cell wall digestion by ruminants. 44,45 However, NDF and ADL as values of leaf blades were much lower than those of stems in all the M. maximus genotypes. This may be because the leaf blade consists mainly of parenchyma cells, while the stems have more sclerenchyma cells.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Moreover, several reports showed that forage growth is accompanied by increased lignin content with secondary cell wall thickening, which limits forage cell wall digestion by ruminants. 44,45 However, NDF and ADL as values of leaf blades were much lower than those of stems in all the M. maximus genotypes. This may be because the leaf blade consists mainly of parenchyma cells, while the stems have more sclerenchyma cells.…”
Section: Discussionmentioning
confidence: 89%
“…who observed a continuous increase in the accumulation of lignin and significant change in its composition in internodes at reproductive stages. Moreover, several reports showed that forage growth is accompanied by increased lignin content with secondary cell wall thickening, which limits forage cell wall digestion by ruminants 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, much research has been carried out on seed dormancy and germination at home and abroad, certain results have been achieved by this [ 26 , 37 , 38 , 39 , 40 , 41 ], but there are still many problems to be solved. Domestic research on seed dormancy is still unsystematic; the research on the seed dormancy of Kobresia mainly focuses on the following: (1) Dormancy breaking is only treated by physical or chemical methods alone; (2) variable temperature is merely combined with other physical or chemical methods; (3) chemical methods for dormancy breaking are very limited, mainly using NaOH, GA 3 , and other reagents; and (4) at present, research on the dormancy and germination mechanism of Kobresia mainly focuses on physiological experiments.…”
Section: Introductionmentioning
confidence: 99%